Employee relations and communication activities of PT. Djelas Tandatangan Bersama during Covid-19 - Sukmaningrum, Lintang Ayu; Moza Laras, Ni Putu Nuke Vinesha; Dellan, Muhammad Rhomy (Faculty of Communication Sciences Universitas Padjadjaran, 2023)
In early 2020, Covid 19 has started to spread to various parts of the world, one of which is Indonesia. So the government made various policies to reduce the spread of the Covid 19 virus. This pandemic also has an impact on employee communication and activities that are felt by PT. Djelas Tandatangan Bersama. This research is based on organizational communication theory. With a qualitative descriptive method of collecting data through in-depth interviews with PT. Djelas Tandatangan Bersama. From the research results obtained employee relations activities and organizational communication of PT. Djelas Tandatangan Bersama during the pandemic was good enough. Because it is supported by the facilities provided by the company to employees when carrying out WFH. So, for employees, communication during a pandemic is not a problem, if the internet network or documents needed are adequate. With the pandemic, PT. Djelas Tandatangan Bersama still wants to be one of the best implementations of electronis cetification companies in Indonesia. Therefore, employees continue to provide new ideas to provide benefits for the company during the pandemic. That with a pandemic like this, are you ready or not ready for this change? However, there are also weaknesses in the communication of employees of PT. Djelas Tandatangan Bersama is the lack of reciprocal communication between employees in the field and the head office. If there is an announcement from the head office that requires feedback from the team in the field, it is often too late.